Development and feasibility of an mHealth intervention for psychoeducational support of Nigerian women diagnosed with breast cancer undergoing chemotherapy: A pilot randomized controlled trial. - Oluwadamilare Akingbade; Ka Yi Hong; Oluwabukola Sharon Ayo; Adetutu Sefinat Alade; Moshood Akinwumi Lawal; Ibironke Elizabeth Somoye; Victoria Adediran; Olamide Sado; Ka Ming Chow (PLoS ONE)
Background Breast cancer (BC) remains a significant health burden globally, with high incidence and mortality rates, particularly in Nigeria. Chemotherapy, a common treatment modality for BC, often leads to various physical and psychological side effects, impacting patients' quality of life. Despite the growing use of mobile health (mHealth) interventions to provide psychoeducational support, there is a paucity of evidence regarding their feasibility and acceptability among Nigerian women with BC. Objective To develop and investigate the feasibility and acceptability of a mHealth psychoeducational intervention (mPEI) named the ChEmo Nurse Breast cancer Application (CENBA) programme. Methods A multi-centre, assessor-blinded, parallel-group pilot randomised controlled trial (RCT) was conducted at Lagos State University Teaching Hospital (LASUTH) and Lagos University Teaching Hospital (LUTH). Thirty women newly diagnosed with BC and undergoing chemotherapy were randomly assigned to an intervention or a control group. The intervention group received the CENBA programme, which included BC education, coping skills training, a discussion forum, and nurse-led consultations, delivered via a mobile application and phone calls over six weeks. The control group received standard care. Feasibility was assessed through consent, attrition, and completion rates, while acceptability was explored via qualitative interviews. Results The completion rate was 93.3%. Qualitative data indicated that participants found the intervention beneficial, particularly appreciating the educational content and the emotional support provided through the discussion forum and nurse consultations. Conclusion The CENBA programme was perceived as a feasible and acceptable mHealth intervention for providing psychoeducational support to Nigerian women with BC undergoing chemotherapy. These findings suggest that the CENBA programme could be a valuable tool in addressing the psychoeducational needs of this population, warranting further investigation in a full-scale RCT. Trial registration This manuscript reports a feasibility study preceding the full trial, which was registered with the United States Clinical Trials registry (number NCT05489354).